Surface modification of Polyether-ether-ketone for enhanced cell response: a chemical etching approach - Dua, Rupak; Sharufa, Onessa; Terry, Joi; Dunn, William; Khurana, Indu; Vadivel, Jagasivamani; Zhang, Yue; Donahue, Henry J. (Frontiers in Bioengineering and Biotechnology, 2023)
Polyether-ether-ketone is increasingly becoming popular in medicine because of its excellent mechanical strength, dimensional stability, and chemical resistance properties. However, PEEK being bioinert, has weak bone osseointegration properties, limiting its clinical applications. In this study, a porous PEEK structure was developed using a chemical etching method with 98 wt% sulfuric acids and three post-treatments were performed. Four groups of PEEK samples were prepared for the study: Control (untreated; Group 1); Etched with sulfuric acid and washed with distilled water (Group 2); Etched with sulfuric acid and washed with acetone and distilled water (Group 3); and Etched with sulfuric acid and washed with 4 wt% sodium hydroxide and distilled water (Group 4). Surface characterization of the different groups was evaluated for surface topology, porosity, roughness, and wettability using various techniques, including scanning electron microscopy, profilometer, and goniometer. Further chemical characterization was done using Energy-dispersive X-ray spectroscopy to analyze the elements on the surface. Bone cell studies were conducted using cell toxicity and alkaline phosphatase activity assays. The SEM analysis of the different groups revealed porous structures in the treatment groups, while the control group showed a flat topology. There was no statistically significant difference between the pore size within the treated groups. This was further confirmed by the roughness values measured with the profilometer. We found a statistically significant increase in the roughness from 7.22  10-3 µm for the control group to the roughness range of 0.1 µm for the treated groups (Groups 2-4). EDX analysis revealed the presence of a 0.1 % weight concentration of sodium on the surface of Group 4, while sulfur weight percentage concentration was 1.1, 0.1, and 1.4 % in groups 2, 3, and 4, respectively, indicating different surface chemistry on the surface due to different post-treatments. Cell toxicity decreased, and ALP activity increased in groups 3 and 4 over seven days compared with the control group. It is demonstrated that the surface modification of PEEK using a chemical etching method with post-processing with either acetone or sodium hydroxide provides a nano-porous structure with improved properties, leading to enhanced osteoblastic cell differentiation and osteogenic potential.